INTENSITY-DURATION-FREQUENCY RELATIONSHIP OF INTENSIVE RAINFALL FOR VILHENA, RONDÔNIA STATE, BRAZIL - Wanderley Muniz Alves, Thallyson; Mozart de Souza Filipaldi, Eden; Marcelo; Fernandes de Souza, Dailton; Pablo Silva Castro, Hemerson (REVISTA GEONORTE, 2024)
Quantifying extreme rainfall, as well as knowing how it is distributed temporally and spatially, is extremely important in the design of hydraulic projects, especially those intended for irrigation, water availability for domestic and industrial supply, and construction works for flooding control and soil erosion. In this work, the IDF relations for the municipality of Vilhena-RO are developed using the Gumbel method and the Choi equation. For the quantification of rainfall, data from 13 consecutive hydrological years from 2008 to 2021 were used. With the daily data, the disaggregation coefficients of CETESB were used. Then, the statistical distribution methodologies of Gumbel and Choi were applied to estimate the maximum rainfall for return times from 1 to 100 years, with durations from 5 to 1440 min and stipulating their maximum intensities. The IDF equations obtained are: i = 942.1863Tr0.1928 (t + 10.515)-0.75118 for the Gumbel method and i = 917.1045Tr0.1671 (t + 10.515)-0.75118 for the Choi equation. The two methodologies applied varied around 2.68% and 10.38% for return times between 1 and 25 years, respectively. The adjustments resulted in the following values for the Gumbel method: K = 942.1863, a = 0.1928, b = 10.515, and c = 0.75118. Using the Choi equation, the results obtained were: K = 917.1045, a = 0.1671, b = 10.515, and c = 0.75118. It is possible to highlight that the maximum intensity values ​​will be higher when calculated by the Gumbel method. Based on the analysis of the IDF graph, more intense rainfall is expected in the first few minutes for longer return periods, especially from 25 years onwards. In addition, higher rainfall volumes are expected for longer duration periods and longer returns.